Ex vivo model of pathological calcification of human aortic valve - Kachanova, O. S.; Boyarskaya, N. V.; Docshin, P. M.; Scherbinin, T. S.; Zubkova, V. G.; Saprankov, V. L.; Uspensky, V. E.; Mitrofanova, L. B.; Malashicheva, A. B. (Frontiers in Cardiovascular Medicine, 2024)
The development of drug therapy for the pathological calcification of the aortic valve is still an open issue due to the lack of effective treatment strategies. Currently, the only option for treating this condition is surgical correction and symptom management. The search for models to study the safety and efficacy of anti-calcifying drugs requires them to not only be as close as possible to in vivo conditions, but also to be flexible with regard to the molecular studies that can be applied to them. The ex vivo model has several advantages, including the ability to study the effect of a drug on human cells while preserving the original structure of the valve. This allows for a better understanding of how different cell types interact within the valve, including non-dividing cells. The aim of this study was to develop a reproducible ex vivo calcification model based on valves from patients with calcific aortic stenosis. We aimed to induce spontaneous calcification in valve tissue fragments under osteogenic conditions, and to demonstrate the possibility of significantly suppressing it using a calcification inhibitor. To validate the model, we tested a Notch inhibitor Crenigacestat (LY3039478), which has been previously shown to have an anti-calcifying effect on interstitial cell of the aortic valve. We demonstrate here an approach to testing calcification inhibitors using an ex vivo model of cultured human aortic valve tissue fragments. Thus, we propose that ex vivo models may warrant further investigation for their utility in studying aortic valve disease and performing pre-clinical assessment of drug efficacy.